1998
DOI: 10.1073/pnas.95.7.3776
|View full text |Cite
|
Sign up to set email alerts
|

Probing the genetic population structure of Trypanosoma cruzi with polymorphic microsatellites

Abstract: We describe here the identification of eight polymorphic microsatellite loci with (CA) n repeats in the Trypanosoma cruzi genome based on the affinity capture of fragments using biotinylated (CA) 12 attached to streptavidincoated magnetic beads. The presence of two peaks in PCR amplification products from individual clones confirmed that T. cruzi is diploid. Hardy-Weinberg and linkage disequilibrium analyses suggested that sexual reproduction is rare or absent and that the population structure is clonal. Sever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
142
0
7

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(166 citation statements)
references
References 23 publications
11
142
0
7
Order By: Relevance
“…1B), implying that they were multiclonal. In our previous study with microsatellites (Oliveira et al 1998) we had only observed more than two peaks in strains obtained from insect vectors, wild mammals or human patients in the acute phase of Chagas disease. Now, with the expanded number of strains from chronic patients we could now observe several cases of more than two peaks, although still at a smaller proportion (Table II).…”
Section: Polymorphism Of Ca-repeats In T Cruzi -mentioning
confidence: 89%
See 2 more Smart Citations
“…1B), implying that they were multiclonal. In our previous study with microsatellites (Oliveira et al 1998) we had only observed more than two peaks in strains obtained from insect vectors, wild mammals or human patients in the acute phase of Chagas disease. Now, with the expanded number of strains from chronic patients we could now observe several cases of more than two peaks, although still at a smaller proportion (Table II).…”
Section: Polymorphism Of Ca-repeats In T Cruzi -mentioning
confidence: 89%
“…Primers sequences have been published previously (Oliveira et al 1998). One primer of each pair was 5'-labeled with fluorescein.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…En esta fase el parasitismo en tejidos es muy alto y restringido a algunos órganos como corazón, músculo esquelético, hígado, esófago, bazo y recto (5,6). La habilidad del parásito para sobrevivir a la fase aguda y avanzar hacia la fase crónica e invadir determinados órganos depende tanto de factores genéticos del parásito como del hospedero (7)(8)(9)(10)(11). Por esto, diversas investigaciones han estudiado la variabilidad genética del parásito y su posible relación con las manifestaciones clínicas de la enfermedad (7).…”
unclassified
“…cruzi es considerado como un organismo diploide, aunque su reproducción es básicamente clonal (5,6); su interacción sexual se restringe a algunas poblaciones selváticas (7). Mediante ensayos con isoenzimas y microsatélites se encontró que las cepas de este protozoo son frecuentemente multiclonales (6,8) y, posiblemente, los pacientes y los vectores se infectan al menos con dos clones genéticamente diferentes (9,10).…”
unclassified